PV SYSTEM FOR PHOTOBIOREACTOR SIZING AND EVALUATION USING TRNSYS SIMULATION - Bambang Susilo; Dimas Firmanda Al Riza; M Bagus Hermanto; Syed Ihtsham Ul Haq Gilani (Journal of Environmental Engineering and Sustainable Technology, 2014)
This paper presents sizing and performance evaluation of a standalone photovoltaic system to supply power of small scale photo-bioreactor system. PSH method is used to determine PV panel and battery capacity, then the sizing results is tested and evaluated using TRNSYS model. The results shows for small scale photobioreactor daily electricity load of 1440 Wh, the PV system requirement is consist of 500 Wp PV panel and 500 Ah battery capacity for 12V system.